Weight and Health Behaviour Changes among Ageing People with Medication for Hypertension and High Cholesterol Level. (6th March 2012) - Sulander, Tommi; Heinonen, Heikki; Karisto, Antti; Valve, Raisa; Pohjolainen, Pertti; Seppälä, Ullamaija; Fogelholm, Mikael
Abstract : Purpose . It is hypothesized that people with medication for hypertension and/or high cholesterol level do not lose weight or change their health behaviour. Methods . This is a six-year follow-up study consisting of 1, 428 individuals from two birth cohorts (1936–40, 1946–50) who took part in clinical check-ups and answered to the survey questionnaires in 2002 and 2008. Results . Those participants, born in 1946–50, who had medication at the baseline had higher increase of body mass index (P < 0.01 ) and waist circumference (P < 0.01 ) at the follow-up. No major disparities in health behaviour changes between medicated and nonmedicated were found. Conclusions . Findings of this study support partly the hypothesis that aging individuals with medication for hypertension and/or high cholesterol level do not lose weight or change their health behaviour.